KONSEP PENDIDIKAN KARAKTER DALAM PERSPEKTIF AL-QUR’AN - sumarni, sumarni (STAI YAPIS Takalar, 2022)
Character education based on ethical values of religious teachings is considered urgent to be promoted as a basic capital to sha- pe human beings who have superior character, play an active role in creating a peaceful society and a dignified nation. Education in the Qur›an strongly emphasizes aspects of morality. The verses that contain emphasis on cognitive are determined by morality, as well as things that are ritualistic, such as prayer which is a ritual aspect directly related to God at the end is to look right and left which symbolizes the necessity to have social care. The concept of education in the Qur›an is implied by the use of the terms tarbiyah, ta›lim, tadris, ta›dib and tazkiyah. From the term, it is understood that the Prophet Muhammad. as a source of exemplary always strives to educate people to be able to read and express the meaning contained in the Qur›an and can practice it. The five terms are important in providing a clear concept for character education in the perspective of the Qur›an, which has the purpose of forming a pious person who has divine values in him. To achieve this goal the Qur›an provides an overview of the use of various approaches, methods and steps in charaacter education. The implementation and results can be seen in the stories of the prophets in inviting and educating their people. Considering that Indonesia is predominantly Muslim, there are two questions to be answered in writing this article: first, what is the concept of character education in the Qur'an; and second, how is the concept of character education in Islamic education. Keyword: Character Education, Al-Qur’an Perspektif